Relationship Between Expression of MAGE-A3 with The Histopathology in NSCLC Patients - Mokhammad Mukhlis; Isnin Anang Marhana (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrounds: Most patients with lung cancer was diagnosted in advanced stage (around 57%). Those diagnosed at early stage were only 15%. To increase the cure rate and life expectancy, lung cancer detection should be performed early. Melanoma-associated antigen 3 (MAGE-A3) is a testicular cancer antigen and is widely expressed in various types of tumor tissue. MAGE-A3 is expressed in about 35-40% of NSCLC. Previous research reported the expression of MAGE-A3 in lung cancer was 30-50%. To detect tumor antigens, CT antigens of the MAGE family can be detected through real time polymerase chain reaction (RT-PCR). This study aimed to analyze the relationship between MAGE A3 expression and histopathology type from forceps biopsy specimens in NSCLC patients. Methods: This study was a cross-sectional study conducted on 14 patients with lung cancer in September 2018 to February 2019. Subjects underwent force biopsy with guidance from bronchoscopy in the pulmonary surgery room Dr. Soetomo. The analysis used was the Fisher's exact test. Results: There were six subjects with histopathology type of adenocarcinoma (42.9%) and eight subjects (57.1%) with the histopathology of squamous cell carcinoma. Expression of MAGE-A3 was positive in 5 subjects (35.7%). Conclusions: There was no significant relationship between the expression of MAGE-A3 and the type of histopathology. (J Respir Indo. 2020; 40(2): 113-9)